Gamified strategy canvas : A novel concept for streamlining strategies through gamification - Tuohiniemi, Lauri (My University, 2024)
Gamification is a concept that has received some attention in the business world for some time now. Using game-like elements in the field of business could provide certainly many kinds of benefits for businesses when implemented correctly. It could provide more motivation among employees and encourage them to improve their skills and work harder. Gamification could also streamline processes and make the conceptualization of strategy clearer to people who are working with strategy. However, without a proper tool to think about the possibilities of gamifi-cation, organizations find it difficult to start thinking about the benefits that gamification could bring. The problem seems to be that there are no real tools that can help businesses think about their strategies from a gamification perspective. This study establishes a new tool that organiza-tions can use to gamify their business processes, strategies, and plans. This research consists of a thorough literature review of the concepts of gamification, strategy, the method of strategy as practice, and the connection between these concepts. Then qualitative research via online inter-view survey was constructed in order to provide a practical view of what needs a new tool should include. The findings provide a concept of a new tool that is based on an existing strategy tool called the business model canvas but modified from it to be very easy to use for businesses and address all the needs that businesses could have based on the interviews. This study provides valuable insight for future research about the connections between gamification and strategy and contributes to the literature by presenting a qualitative analysis of the use of gamification and problems in strategy implementation as well as a thorough literature review of the existing literature about gamification and strategies and how they are connected.
Keywords: gamification; enterprises; strategies; corporate strategies; strategic planning; business; strategic leadership; leadership (activity); organisations (systems); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development